The Implications of Globalization for Firms' Demand for Skilled and Unskilled Labor - Christian Scheuer; Anders Sørensen; Michael Rosholm (Copenhagen Business School (CBS), Department of Economics, 2007)
This paper investigates the impact of globalization, in the sense of increasing international trade, on the demand for skills in Danish manufacturing companies. The study is based on a unique data set that enables us to develop rich measures of international outsourcing and import penetration. Moreover, the data also allows several strategies to strengthen the causal interpretation of our results. The main finding of the analysis is that it is of crucial importance to distinguish imports - both in the form of outsourcing and overall imports - by country-of-origin. We find that international trade with low-wage countries leads to skill-upgrading. This is especially pronounced for import penetration with a ceteris paribus contribution of around fifty percent to skill-upgrading. Moreover, we find that import penetration in goods originating from high-wage countries lead to skill-downgrading. This latter result suggests that Danish manufacturing has comparative advantage in skillintensive production when compared to low-wage countries, but in unskill-intensive production when compared to high-wage countries.
hdl:10398/7625
Keywords: F14; J24; L60; 330; Skill-upgrading; Low-wage country outsourcing; Low-wage country import penetration; Comparative advantage